2015
DOI: 10.2987/moco-31-03-233-241.1
|View full text |Cite
|
Sign up to set email alerts
|

La Crosse Encephalitis Virus Infection in Field-CollectedAedes albopictus,Aedes japonicus, andAedes triseriatusin Tennessee

Abstract: La Crosse virus (LACV) is a mosquito-borne virus and a major cause of pediatric encephalitis in the USA. La Crosse virus emerged in Tennessee and other states in the Appalachian region in 1997. We investigated LACV infection rates and seasonal abundances of the native mosquito vector, Aedes triseriatus, and 2 recently introduced mosquito species, Ae. albopictus and Ae. japonicus, in an emerging disease focus in Tennessee. Mosquitoes were collected using multiple trapping methods specific for Aedes mosquitoes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 31 publications
1
66
0
Order By: Relevance
“…Given that transmission studies can be highly variable and that, since introduction of the tiger mosquito into the United States, local LACV strains may have adapted to be more suitable in this new host, it is also possible that our estimates for tiger mosquito competence are overly low (see Conditions Under Which Tiger Mosquitoes Enable LAC Spread, at http://www.clfs.umd.edu/biology/faganlab/disease-ecology.html). Recent evidence finding substantial infection rates in a tiger mosquito population in Tennessee ( 33 ) supports this conclusion, although further transmission studies and analyses of virus evolution are warranted.…”
Section: Discussionmentioning
confidence: 95%
“…Given that transmission studies can be highly variable and that, since introduction of the tiger mosquito into the United States, local LACV strains may have adapted to be more suitable in this new host, it is also possible that our estimates for tiger mosquito competence are overly low (see Conditions Under Which Tiger Mosquitoes Enable LAC Spread, at http://www.clfs.umd.edu/biology/faganlab/disease-ecology.html). Recent evidence finding substantial infection rates in a tiger mosquito population in Tennessee ( 33 ) supports this conclusion, although further transmission studies and analyses of virus evolution are warranted.…”
Section: Discussionmentioning
confidence: 95%
“…albopictus and Ae. japonicus has likely expanded the distribution of LACV from the rural environment to the urban and suburban environment as both species have been recovered in field collections as infected with LACV (Gerhardt et al 2001, Harris et al 2015, Westby et al 2015. Previous surveillance studies have suggested a change in the composition of Ae.…”
Section: Discussionmentioning
confidence: 95%
“…triseriatus and Ae. albopictus, which may be due to the use of different trapping methods or could indicate a change in the ratio of these vector species (Westby et al 2015). Continued monitoring of these species and evaluation of different trapping methods are necessary for answering those questions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations